Intersections of the political: Catholicism, nationalism and parties in Rio Cuarto in the mid-20th century (Res Gesta, 2020)
With the objective of evidencing the porosity and complexity of the links and crossings between the political and the religious, in the present article we carry out the reconstruction and analysis of the evolution between the thirties and the fifties of a political segment -constituted in the intersection of multiple ambits of participation in the public sphere- that had a sustained permanence in the political life of Rio Cuarto. We propose a reduced scale of analysis, from a perspective centered on daily political practices in a relational fabric that transcended the diversity of the eventual governments that succeeded each other in the period studied and that -we understand- managed to permeate in the long term the gazes of the political.
Keywords: politics; Catholicism; nationalism; peronism